2008
DOI: 10.1002/ejoc.200800638
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Amination and Sulfonylation of 5‐Bromo‐3‐[2‐(diethylamino)ethoxy]indoles to Potential 5‐HT6 Receptor Ligands

Abstract: A general and efficient palladium-catalyzed amination of 5-bromo-3-[2-(diethylamino)ethoxy]indoles has been developed. Best results are obtained in the presence of Pd(OAc) 2 and 2-[di(1-adamantyl)phosphanyl]-1-phenylpyrrole as ligand. Subsequent sulfonylation gave novel indole deriva-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The amination and amidation of N-protected bromoindoles were reported to occur in moderate to high yields by using, respectively, Pd 2 (dba) 3 ·CHCl 3 /2-[di( tert -butyl)phosphino]biphenyl and Pd 2 (dba) 3 ·CHCl 3 /Xantphos [or 3,5-(CF 3 ) 2 Xantphos] . N-Protected 5-bromo-3-[2-(diethylamino)ethoxy]indoles were subjected to amination reactions in the presence of Pd(OAc) 2 , 1-phenyl-2-[di(1-adamantyl)phosphanyl]pyrrole as ligand, and LiHMDS (or Cs 2 CO 3 ) at 100 °C for 20 h in toluene . The amination of N-protected indoles was also performed under microwave-assisted conditions.…”
Section: Functionalization Of the Preformed Indole Systemmentioning
confidence: 99%
“…The amination and amidation of N-protected bromoindoles were reported to occur in moderate to high yields by using, respectively, Pd 2 (dba) 3 ·CHCl 3 /2-[di( tert -butyl)phosphino]biphenyl and Pd 2 (dba) 3 ·CHCl 3 /Xantphos [or 3,5-(CF 3 ) 2 Xantphos] . N-Protected 5-bromo-3-[2-(diethylamino)ethoxy]indoles were subjected to amination reactions in the presence of Pd(OAc) 2 , 1-phenyl-2-[di(1-adamantyl)phosphanyl]pyrrole as ligand, and LiHMDS (or Cs 2 CO 3 ) at 100 °C for 20 h in toluene . The amination of N-protected indoles was also performed under microwave-assisted conditions.…”
Section: Functionalization Of the Preformed Indole Systemmentioning
confidence: 99%
“…In 2008, Beller and co-workers continued to develop an efficient Pd-catalyzed amination protocol for 5-bromo-3-[2-(diethylamino)ethoxy]indoles using the reported Pd/ L2d system. 49 Biologically active 5-hydroxytryptamine 6 (5-HT 6 ) 50 receptor ligands were successfully synthesized by subsequent sulfonylation of these indoles. The 5-HT 6 receptor ligands are known to facilitate the reduction of food intake, fat absorption, and body weight.…”
Section: Scheme 46 Substrate Scope Of the Pd/bippyphos L11a System Inmentioning
confidence: 99%
“…Although palladium catalyzed C–N bond-forming reactions were initially developed using phosphine ligands, recent work has shown that other types of ligands are also effective partners for these transformations, predominantly N -heterocyclic carbene (NHC) ligands and more rarely exotic ligands such as ylides. Beller-type ligands, based on a dialkylphosphinoimidazole scaffold, have also proven to be highly effective ligands, particularly for the synthesis of important pharmaceutical targets. , In addition, the use of bidentate phosphine ligands frequently has several advantages such as lower catalyst loadings and improved turnover numbers …”
Section: Introductionmentioning
confidence: 99%